Reading Motivation, Reading Habits, Word Recognition, And Reading Comprehension of Grade 5 Pupils in Public Elementary Schools - Panganiban, Gladys; Hucalinas, Merfe; Madrigal, Dennis (Technium Social Sciences Journal, 2025)
This study explored the correlations between reading motivation, reading habits, word recognition, and reading comprehension among elementary pupils in a southern district of Negros Occidental. A total of 365 participants were involved in the study. The study revealed a significant correlation between reading motivation and reading habits, reading motivation and word recognition, reading motivation and reading comprehension, and word recognition and reading comprehension. No significant correlation was found between reading habits and word recognition, nor between reading habits and reading comprehension. Word recognition emerged as the only predictor of reading comprehension. These findings supported Krashen's Second Language Acquisition (SLA) theory. The study concluded that 74% of participants did not meet the grade-level reading requirements, underscoring the need for effective reading intervention programs. The findings suggested that enhancing reading motivation, habits, and word recognition could significantly improve reading comprehension, and that these factors should be integrated into the development of targeted reading programs.